Conjugated Polyamines in Root Plasma Membrane Enhanced the Tolerance of Plum Seedling to Osmotic Stress by Stabilizing Membrane Structure and Therefore Elevating H+-ATPase Activity - Du, Hongyang; Chen, Benxue; Li, Qiang; Liu, Huaipan; Kurtenbach, Ronald (Frontiers in Plant Science, 2022)
Polyamines (PAs) are small positively charged molecules in plants and play important functions in many biological processes under various environmental stresses. One of the most confounding problems relating to PAs in stresses is the lack of understanding of the mechanisms underlying their function(s). Furthermore, a limited number of studies have addressed this issue at the sub-cellular level, especially in tree plants under drought stress. So, in this research, by simulating natural drought stress with polyethylene glycol (PEG) osmotic stress, the relationship between the levels of conjugated polyamines and the activity of H+-ATPase in plasma membrane was elucidated with the roots of two plum (Prunus salicina L.) cultivars, which were different in drought tolerance, as experimental materials. Furthermore, free PA levels and the activities of S-adenosylmethionine decarboxylase (SAMDC) and transglutaminase (TGase), which were closely associated with the levels of free and conjugated PAs, were also detected. Results showed that under osmotic stress, the increases of the levels of non-covalently conjugated (non-CC) spermidine (Spd) and spermine (Spm), covalently conjugated (CC) putrescine (Put) and Spd in plasma membrane of drought-tolerant Ganli No. 5 were more significant than those of drought-sensitive Suli No. 3, indicating that these conjugated PAs might be involved in the tolerance of plum seedlings to stress. Furthermore, the conjugated PAs were closely correlated with plum seedling growth, water retention capacity, plasma membrane damage degree, and H+-ATPase activity in plasma membrane. To get more complementary evidences, we subjected plum seedlings to combined treatments of PEG and exogenous PA (Spd or Spm), and an inhibitor of SAMDC (methylglyoxal-bis guanylhydrazone MGBG) or TGase (o-phenanthrolin). These results collectively suggested that non-CC Spd and Spm, CC Put and Spd in plasma membrane might function in enhancing the tolerance of plum seedlings to osmotic stress by stabilizing membrane structure and therefore elevating H+-ATPase activity.